2010
DOI: 10.5713/ajas.2010.90403
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Fermentation Quality of Rice Straw Silage by Application of a Bacterial Inoculant and Glucose

Abstract: The improvement of the fermentation quality of rice straw silage by application of lactic acid bacteria (LAB) and glucose was investigated in this study. Sixteen rice varieties were harvested at the maturity stage and the rice straw was ensiled with LAB inoculant (1×10 5 cfu/g of fresh weight) and glucose (2% of fresh weight). Inoculation with LAB improved the fermentation as reflected in reductions in pH, acetic acid (by 3.7 to 78.3%), butyric acid (by -6.0 to 100.0%) and ammonia nitrogen (by 1.0 to 71.7%) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
35
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 15 publications
12
35
2
1
Order By: Relevance
“…Ratnakomala et al (2006) reported that the addition of LAB (L. plantarum 1A-2) for elephant grass silage resulted in lower pH and higher lactic acid. Similar findings have also been reported by Li et al (2010) using L. plantarum for rice straw silage, Filya et al (2007) for alfalfa silage, and Kung et al (2003) using LAB (Lactobacillus buchneri 40788) for alfalfa silage can reduce the pH and proteolysis. The low acidity created by lactic acid bacteria inhibits the growth of unwanted bacteria.…”
Section: Complete Feed Silage Qualitysupporting
confidence: 85%
“…Ratnakomala et al (2006) reported that the addition of LAB (L. plantarum 1A-2) for elephant grass silage resulted in lower pH and higher lactic acid. Similar findings have also been reported by Li et al (2010) using L. plantarum for rice straw silage, Filya et al (2007) for alfalfa silage, and Kung et al (2003) using LAB (Lactobacillus buchneri 40788) for alfalfa silage can reduce the pH and proteolysis. The low acidity created by lactic acid bacteria inhibits the growth of unwanted bacteria.…”
Section: Complete Feed Silage Qualitysupporting
confidence: 85%
“…Rice is one of the most important crops in the world, and the annual production of rice straws is more than 192 million tons in China (LI et al, 2010). Most of rice straw is incinerated or disposed as compost, which causes resources wasting and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low water soluble carbohydrates (WSC) content in straw, tremendous efforts have been made to improve fermentation quality and nutritive value of straw silage by supplying fermentation substrate directly or indirectly (LI et al, 2010, ZHANG et al, 2010. Molasses has been proven to be an effective silage additive by promoting lactic acid bacteria fermentation, reducing silage pH, discouraging clostridia fermentation and proteolysis, and generally decreasing organic matter losses when applied to crops with low water soluble carbohydrates (WSC) (BOLSEN et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…dan Acenitobacter sp. Sedangkan hasil penelitian fermentasi jerami padi oleh Li et al (2010) dengan menggunakan Lactobacillus plantarum dengan penambahan glukosa menunjukkan terjadinya peningkatan nilai nutrisinya. Kombinasi bakteri Clostridium sp., Bacillus sp., dan Geobacillus sp yang digunakan pada proses fermentasi selama 9 hari mampu mengurai kandungan lignoselulose dalam jerami padi (Zhao et al, 2014).…”
Section: Metode Peningkatan Nilai Nutrisi Jeramiunclassified